Association of vitamin D with blood pressure and obesity in prinzmetal angina - Kheirouri, Sorayya; Mohajeri, Mahsa; Avesta, Leili (Progress in Nutrition, 2019)
Vitamin D deficiency is a main risk factor for cardiovascular disease. Low serum vitamin D can increase blood pressure and weight in person. A case–control study was conducted on 69 matched pairs, aged 40-60 years. Vitamin D was measured by Chemi-luminescence immunoassay method. There was significant difference in serum 25- Hydroxy vitamin D between groups of study (P= 0.0001). The mean ± SD of 25-Hydroxy vitamin D in prinzmetal angina was 12.16 ± 5.21 and in healthy persons was 23.44 ± 2.52 ng/ml. Between vitamin D and waist circumference there was significant association in prinzmetal patients (p= 0.04, ß= 0.236). There was not significant relation between vitamin D with blood pressure and BMI in study participants (P≥0.05). Vitamin D can effect on obesity in prinzmetal angina patients.